Call to action: recognize and prevent the effects of extreme heat on early childhood development and health - Vanitha Sampath; Devon Payne-Sturges; Natalie Slopen; Nathaniel Harnett; Nathaniel Harnett; Alison G. Lee; Kari Nadeau; Nat Kendall Taylor; Lindsey Burghardt; Lindsey Burghardt (Frontiers in Public Health)
The frequency and severity of heat waves are expected to worsen with climate change. Exposure to extreme heat, or prolonged unusually high temperatures, are associated with increased morbidity and mortality. The fetus, infant, and young child are more sensitive to higher temperatures than older children and most adults given that they are rapidly developing. During pregnancy, exposure to extreme heat may result in dehydration, inflammation, and reduced blood flow in the placenta potentially triggering preterm birth and increased rates of stillbirth and low birth weight infants. Young children experience a range of immediate health effects from heat, including disruptions in their sleep and learning, and exacerbations of asthma. Long-term impacts include lower cognitive function, reduced ability to concentrate, and adverse outcomes in mental and behavioral health. It is possible to protect children by taking steps to reduce the potential long-term harm of increasing exposure to extreme heat, such as implementing early warning systems, establishing community cooling centers, and expanding support programs to provide cooling systems to homes. Further, adapting existing infrastructure to withstand increased heat through increasing shade as well as the use of cool pavements or cool/green roofs in early care centers and other places children spend time may be efficient ways of mitigating the developmental effects of extreme heat. Finally, preventing future temperature increases by addressing the root causes behind our rapidly heating planet by decreasing use of fossil fuel and investing in renewable energy sources are ultimately needed to ensure healthy child development.